Mechanisms and Therapeutic Targets of Cardiac Regeneration: Closing the Age Gap - Castellan, Raphael F. P.; Meloni, Marco (Frontiers in Cardiovascular Medicine, 2018)
Whereas a regenerative response is limited in the mammalian adult heart, it has been recently shown that the neonatal mammalian heart possesses a marked but transient capacity for regeneration after cardiac injury, including myocardial infarction. These findings evidence that the mammalian heart still retain a regenerative capacity and highlight the concept that the expression of distinct molecular switches (that activate or inhibit cellular mechanisms regulating tissue development and regeneration) vary during different stages of life, indicating that cardiac regeneration is an age-dependent process. Thus, understanding the mechanisms underpinning regeneration in the neonatal infarcted heart is crucial to develop new treatments aimed at improving cardiovascular regeneration in the adult. The present review summarises the current knowledge on the pathways and factors that are known to determine cardiac regeneration in the neonatal infarcted heart. In particular, we will focus on the effects of microRNAs manipulation in regulating cardiomyocyte proliferation and regeneration, as well as on the role of the Hippo signalling pathway and Meis1 in the regenerative response of the neonatal infarcted heart. We will also briefly comment on the role of macrophages in scar formation of the adult infarcted heart or their contribution for scar-free regeneration of the neonatal mouse heart after myocardial infarction. Although additional research is needed in order to identify other factors that regulate cardiovascular regeneration, these pathways represent potential therapeutic targets for rejuvenation of aging hearts and for improving regeneration of the adult infarcted heart.